Analyzing Heat Transfer Variations with Hole Quantities in Multi-Layered Flat-Plate Cooling Towers - Thaib, Razali; Syuhada, Ahmad; Perangin-Angin, Alifia Kaneysha; Al Kautsar, Teuku Muhammad Aldine (Politeknik Negeri Lhokseumawe, 2025)
Cooling towers are essential industrial heat exchangers that cool water by exposing it to air, promoting evaporation and subsequent temperature reduction. Despite extensive research on performance enhancement, the optimal design configuration remains uncertain. This study examines the impact of hole quantity and shape on the thermal performance of a multi-layered flat-plate cooling tower. Circular holes in three configurations—80, 120, and 185 holes—were tested at inlet temperatures of 65°C and 75°C. The cooling tower has a total height of 2.4 meters, with each plate measuring 0.7 × 0.5 meters and arranged at a 15° angle. Experimental results show that the highest heat transfer rate occurs at 75°C with 185 holes, while the largest heat transfer coefficient is achieved at 65°C with the same configuration. These findings emphasize the significant role of hole quantity and geometry in optimizing cooling tower performance. The results offer valuable insights for industrial applications, particularly in improving cooling efficiency in power plants and manufacturing processes.